The Effectiveness of Using Aloe Vera Facial Soap and Aloe Gel on the Degree of Acne Vulgaris in Students of SMA Negeri 2 Bayang - Putri Bunga Anggreno Setiawan; Ade Teti Vani; Budi Yulhasfi Febrianto; Vina Tri Septiana (Jurnal EduHealth, 2020)
Acne vulgaris is an inflammatory skin condition caused by polysebaceous units that occurs in adolescents and young adults characterized by comedones, papules, pustules, and nodules. Records of the Indonesian cosmetic dermatology study group showed 60% of acne vulgaris sufferers in 2006 and 80% in 2007. Accur acne vulgaris 80 to 100% in young adults, namely 14-17 years in women, and 16-19 years in men. One of the plants that are useful as facial wash aloe vera. Aloe vera as an ingredient in making soap, is not only able to kill bacteria, but also can smooth the skin.Objective: to find the effectiveness application aloe vera facial wash and aloe vera gel between the degree of acne vulgaris in student at SMA Negeri 2 Bayang. Methods: The scope of this research includes pharmacology and dermatology. Located of this research will be at SMA Negeri 2 Bayang Pesisir Selatan. The time of the research was carried out in April 2021. This type of research is a form of experiment pre-test and post-test control group design. The target population in this research were students of SMA Negeri 2 Bayang Pesisir Selatan who suffered from acne vulgaris on the facial skin. Data analysis using paired sample t test and independent t test. Result: most students are 17 years old 8 people (40%), the most gender are women as many as 18 people (90%), there is a effectiveness between the use of aloe vera facial wash and aloe vera gel with the degree of acne vulgaris in students at SMA Negeri 2 Bayang. (P = 0.000) and there is a effectiveness between the use of aloe vera facial wash and the degree of acne vulgaris in students at SMA Negeri 2 Bayang. (P=0.040). Conclusion: there is a the effectiveness application aloe vera facial wash and aloe vera gel between the degree of acne vulgaris in students at SMA Negeri 2 Bayang.